2007
DOI: 10.1111/j.1467-9353.2007.00365.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Conjunctive Use of Surface and Groundwater with Recharge and Return Flows: Dynamic and Spatial Patterns

Abstract: scarcity and the environmental impact of water use is a topic of growing concern. Improving efficiency in irrigation water allocation, in terms of both scarcity and environmental impact, has drawn considerable attention from many economists and planners. Traditional studies usually model water allocation assuming that the users are independent. However, many early water resource economists pointed out the interdependency in water users (Hartman and Seastone; Johnson, Gisser, and Werner; and O'mara). Considerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Azaiez [2] develops a multi-stage model to determine how much surface water must be imported for irrigation and to arti…cially recharge the aquifer, which is also and simultaneously used for irrigation. Pongkijvorasin and Roumasset [26] develop an optimal control model where groundwater users enjoy positive externalities from canal conveyance loss and from return ‡ows to the aquifer from irrigation. But, these studies still consider surface and groundwater as two separate entities, only related by the fact that some surface water is lost to deep percolation or is used for aquifer recharge, representing positive externalities on the aquifer.…”
Section: Background Of Groundwater Managementmentioning
confidence: 99%
“…Azaiez [2] develops a multi-stage model to determine how much surface water must be imported for irrigation and to arti…cially recharge the aquifer, which is also and simultaneously used for irrigation. Pongkijvorasin and Roumasset [26] develop an optimal control model where groundwater users enjoy positive externalities from canal conveyance loss and from return ‡ows to the aquifer from irrigation. But, these studies still consider surface and groundwater as two separate entities, only related by the fact that some surface water is lost to deep percolation or is used for aquifer recharge, representing positive externalities on the aquifer.…”
Section: Background Of Groundwater Managementmentioning
confidence: 99%
“…One strand of the literature deals with optimal management of multiple groundwater resources (see Wada 2012 or Zeitouni andDinar 1997). Another strand studies the conjunctive use of ground and surface water (see Burt 1964;Chakravorty and Umetsu 2003;Gemma and Tsur 2007;Knapp and Olson 1995;Krulce et al 1997;Pongkijvorasin and Roumasset 2007;Stahn and Tomini 2009, 2011or Tsur and Graham-Tomasi 1991. Roumasset and Wada (2012) showed that optimal management of several independent groundwater resources depend on their marginal opportunity cost: only the resource with the lowest marginal opportunity cost is used initially, whereas in the steady state, all resources are used.…”
Section: Introductionmentioning
confidence: 98%